2013
DOI: 10.1016/j.cej.2013.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of chitosans for the treatment of papermaking process water by dissolved air flotation

Abstract: Interest has grown in bio-polymers as being environmental friendly alternatives to synthetic additives. In this work, two native chitosans with different molecular weights have been evaluated on a laboratory scale for their effectiveness for the removal of contaminants from papermaking process waters by dissolved air flotation (DAF). The use of chitosan quaternary derivatives and the use of the native chitosans in combination with anionic bentonite microparticles have also been tested. Results demonstrate a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…Rodrigues et al (2008) reported that the chitosan treatment favored settling and the formation of a dense sludge. Miranda et al (2013) showed the efficiency of chitosans for the treatment of process water by DAF. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rodrigues et al (2008) reported that the chitosan treatment favored settling and the formation of a dense sludge. Miranda et al (2013) showed the efficiency of chitosans for the treatment of process water by DAF. …”
mentioning
confidence: 99%
“…The charge demand corresponds to the amount of a strongly charged polyelectrolyte that needs to be added to reach a charge-neutral condition of the surfaces (Rasteiro et al 2008; Blanco et al 2002a,b). This approach has been used to optimize dissolved air flotation systems for pulp and paper mills (Negro et al 2005; Saarimaa et al 2006a,b;Miranda et al 2008Miranda et al , 2009bMiranda et al , 2013. …”
mentioning
confidence: 99%
“…It also has a unique set of properties such as natural cationic charge density, biodegradability, biocompatibility, non-toxicity, and antimicrobial activity (Crini and Badot 2008;Renault et al 2009;Thakur and Thakur 2014). These specific properties make it suitable for a large range of applications, including coagulationflocculation processes (Bratskaya et al 2004;Renault et al 2009;Zemmouri et al 2011;Miranda et al 2013;Yang et al 2016). The most relevant characteristics of chitosan in relation to flocculation are charge density (related to its deacetylation degree), molecular weight, and molecular structure (Renault et al 2009;Thakur and Thakur 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been no studies regarding the possible combination of chitosan with other typical components of microparticle retention systems, such as bentonite. Some previous works, which focused on process waters and wastewaters, have demonstrated that bentonite improves the size and density of flocs formed with chitosan, thus increasing flocculation rate (Roussy et al 2005a,b;Cai et al 2010;Miranda et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation